Synthesis and dark toxicity of 5-(4-carboxyphenyl)-10, 15, 20-tris(phenyl)-porphyrinato chlorido gallium(III) when conjugated to δ-aminolevulinic acid. Issue 20 (17th October 2016) - Managa, Muthumuni; Mkhize, Scebi; Britton, Jonathan; Prinsloo, Earl; Nyokong, Tebello
Abstract: 5-(4-Carboxyphenyl)-10, 15, 20-tris(phenyl)-porphyrinato chlorido gallium(III) (2 ) was synthesized and then linked to ethyl ester δ-aminolevulinic acid to form3 . There was no shift in Soret band following conjugation. The fluorescence and singlet oxygen generating behavior of the porphyrins were also investigated. The highest singlet oxygen quantum yield (ΦΔ ) obtained was that of3 . Complexes2 and3 as well as metal free 5-(4-carboxyphenyl)-10, 15, 20-tris(phenyl)-porphyrinato showed no dark toxicity on MCF-7 breast cancer cells. Abstract :